AHP Scoring and Weighting Main Criteria For Assessment of Potential Hydrometeorological Disasters: A Literature Study - Octo Mario Pasaribu; Aris Poniman; Andrian Andaya Lestari; Yosef Prihanto; Asep Adang Supriyadi; Trismadi Trismadi (Journal of Applied Geospatial Information, 2023)
In general, the territory of Indonesia is prone to hydrometeorological disaster events. In disaster management, it is necessary to map the source or level of potential disaster hazards. The Analytic Hierarchy Process (AHP) method has been used to determine the relative importance of each criterion for potential mapping disasters. This literature study aims to determine the criteria and weighting in the AHP approach that can be used in assessing the potential for hydrometeorological disasters. This literature review is limited by analyzing and assessing the potential, vulnerability, and vulnerability of floods, landslides, and tornadoes using the AHP method. The input data used in the literature is based on the opinions of experts, interested stakeholders, and related regulations to determine the criteria and their weighting. The results of this literature review show that the three criteria are the dominant determining factors in assessing and analysing the three hydrometeorological disasters. The scoring of each criterion is based on its impact on the disaster.